Influence of Digital Leadership, Environmental Awareness, and Organizational Learning on Sustainable Supply Chain Performance through Green Supply Chain Innovation - Puan Arthemisia; Gatri Lunarindiah; Wahyuningsih Santosa; Dorina Widowati; Ratna Darasih (Manunggal Halim Jaya, 2026)
awareness, and organizational learning on sustainable supply chain performance through green supply chain innovation. This research was conducted in the cosmetics manufacturing industry in Ciledug, South Jakarta, Indonesia. A quantitative approach was used, with data collected from 240 employees involved in supply chain activities using purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that digital leadership, environmental awareness, and organizational learning have a positive and significant effect on green supply chain innovation. Green supply chain innovation also has a significant positive effect on sustainable supply chain performance and mediates the relationship between the independent variables and sustainable supply chain performance. These findings highlight the importance of digital leadership, environmental awareness, and organizational learning in improving sustainable supply chain performance through green innovation. This study provides practical insights for managers to strengthen digital capabilities and sustainability practices and contributes to the sustainable supply chain management literature.